Hepatitis Delta Prevalence in South America: A Systematic Review and Meta-Analysis - Scarponi, Cristiane Faria de Oliveira; Silva, Raquel Duarte Nunes da; Souza Filho, Job Alves de; Guerra, Maria Regina Lage; Pedrosa, Marco Antônio Ferreira; Mol, Marcos Paulo Gomes (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Hepatitis delta virus (HDV) has been associated with acute or chronic hepatitis in Latin America, but there is no prevalence study covering South American countries. This meta-analysis aimed to estimate anti-HDV prevalence through a systematic review of published articles in English, Portuguese and Spanish until December 2017. Searches were conducted in Health Virtual Library, Capes, Lilacs, PubMed, and SciELO, according to defined criteria regarding participant selection and geographical setting. Study quality was assessed using the GRADE guidelines. Pooled anti-HDV prevalence was calculated using the DerSimonian-Laird random-effects model with Freeman-Tukey double arcsine transformation. Out of the 405 identified articles, only 31 met the eligibility criteria for inclusion in the meta-analysis. In South America, pooled anti-HDV prevalence among hepatitis B virus carriers was 22.37% (95% confidence interval: 13.72-32.26), though it appeared less frequently in some countries and populations, according to the data collection date. The findings indicated significant successive reductions in anti-HDV prevalence over thirty years. However, there was a scarcity of HDV epidemiological studies outside the Amazon Basin, notably in the Southwest continent and absence of target population standardization. There was a high HDV prevalence in South American countries, despite differences in methodological characteristics and outcomes, highlighting a drastic decline in the last decades. Future studies should identify HDV prevalence estimates in other regions of the continent and identify risk factors.